Bibliometric Analysis of Statistical Data Processing Using SPSS - Anastasya, Diva Berta; Yuadi, Imam (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2024)
This article conducts a thorough bibliometric analysis to explore the theme of "Statistical Data Processing Using SPSS," sourced from the Web of Science. Statistical analysis, essential in research, employs various methods, particularly for statistical data processing. Among the tools available for quantitative data analysis, SPSS (Statistical Package for Social Science) is prominently used. This study aims to analyze the efficiency and accuracy of SPSS in processing data, facilitating researchers in understanding relationships between variables for enhanced data-driven decision-making. The method involved searching data on the Web of Science and employing Biblioshiny for the bibliometric analysis. The analysis resulted in visualizations that categorized field data based on keywords, publication levels, regional distribution, and several relevant document types, covering 500 documents dated from 1991 to 2023. The findings indicate an annual growth rate of 13.14% and an average document age of 6.08 years. The study concludes that SPSS offers a precise tool for testing quantitative research data, underscoring its utility in statistical data processing